Pengembangan Lembar Kerja Peserta Didik Instalasi Motor Listrik - Afriadi, Defri; Husnaini, Irma (Jurnal Pendidikan Teknik Elektro, 2024)
Student Worksheet (LKPD) is one of the learning media educators use to convey practical learning material. This research is motivated by learning media on the subject of Electric Motor Installation which is still minimal and the learning model used is still teacher-centered which causes learning outcomes to be not optimal. This study aims to develop LKPDs for Electrical Motor Installation subjects that are valid, practical, and effective so that they can improve practicum learning. This research uses the type of R&D (research and development) development with the 4-D model which consists of four stages of development, namely defining, designing, developing, and distributing. The data collection instrument uses an evaluation sheet in the form of a questionnaire for validity and practicality data. At the same time, effectiveness is seen in the practical learning outcomes when using LKPD. Based on the validation assessment by the material expert, the validator obtained a valid value, while the assessment of the media expert validator obtained a valid category value. The practicality assessment conducted by the subject teacher was rated as very practical, and then the assessment of the students was rated as very practical. Assessment of the effectiveness of practicum learning outcomes to obtain an effective value. It can be concluded that the LKPD for Electric Motor Installation is suitable for use in practicum learning because it has been declared valid, practical, and effective.